The effects of Psychological Contract Breach on Organizational Citizenship Behavior: A moderating effect of affectivity - Park, Jieun; Oh, Wonkung; Kim, MinSoo (Korean Journal of Industrial and Organizational Psychology, 2012)
This study examined that the role of dispositional affectivity in the relationship between psychological contract breach and organizational citizenship behavior (OCB). Based on data from 318 employees, we found that when the levels of promised and delivered inducements of psychological contract breach are equal, employees’ OCB increases the absolute levels of two types of inducements increase. Furthermore, we found that dispositional affectivity moderated the relationship between psychological contract breach and OCB. While positive affectivity strengthened the relationship between the delivered inducements of breach and OCB, negative affectivity moderated the relationship between the promised inducements of breach and OCB. These results contribute the psychological contract literature and employment relationship. Implications are discussed and directions for future research are provided.